Application of response surface methodology (RSM) for optimization of hydrogen sulphide adsorption using coconut shell activated carbon xerogel: effect of adsorption pressure and hydrogen sulphide flowrate - Saleh, Ali Mohammed; Mahdi, Hadi Hamdi; Alias, Azil Bahari; Ali, Obed M.; Wan Ab Karim Ghani, Wan Azlina; Abdulwahhab Shihab, Thaer; Syed Hasan, Syed Shatir A.; Ahmed, Omer Khalil; Mohammed Saleh, Noah (Lavoisier, 2024)
To improve the adsorption of hydrogen sulfide (H2S) by using coconut shell-activated carbon xerogel (CSACX), we adopted the response surface methodology (RSM) with a central composite design (CCD). This material was created by incorporating a cross-linker agent, initiator agent, and polymer. The process of creating CSACX involved synthesizing coconut shell activated carbon into a wet gel using chemicals such as sodium alginate, calcium carbonate, glucono delta-lactone (GDL), and distilled water in a sol-gel method to obtain a xerogel. Afterward, the gel was dried in an oven at 60℃ for 24 hours. Subsequently, it was used as an adsorbent for the adsorption test. The adsorption test was conducted at two different initial concentrations of H2S, 25 ppm, and 50 ppm, to assess the effectiveness of H2S removal at different concentrations. In the RSM approach, we selected adsorption pressure (1-3 bar) and H2S flow rate (100-300 L/hr) as the process variables while maintaining a constant contact time (5 minutes), adsorbent weight (11 g) and temperature (30℃). The removal efficiency of H2S (%) was chosen as the response. Our findings showed that the optimum conditions for H2S removal were at 1 bar and 100 L/hr for 25 ppm of H2S and 1 bar and 100.3830 L/hr for 50 ppm of H2S. The model generated from RSM predicted that maximum H2S removal can be achieved at a lower pressure and flow rate for any H2S initial concentration.